Peningkatan Kesadaran Lingkungan Siswa SMA Negeri 2 Padang Bolak Melalui Pelatihan Pembuatan Pupuk Organik Cair - Endah Cahyani Simamora; Raja Aminuddin Siregar; Zulfahmi Zulfahmi; Ari Andani Nasution; Ulina Hutasuhut; Gina Sonia Harahap (Institut Nalanda, 2026)
Organic waste management remains a significant environmental issue, particularly in school settings, where waste from daily activities is not managed effectively. Improper management of organic waste may contribute to environmental pollution and reduce ecosystem quality. This activity aimed to enhance students' environmental awareness through training on the production of liquid organic fertiliser (LOF) derived from organic waste at SMA Negeri 2 Padang Bolak, North Padang Lawas Regency. The activity was implemented through several stages, including the delivery of educational materials, demonstrations of LOF production, direct practical activities, and mentoring in the application of LOF to plants within the school environment. The LOF production process utilised vegetable and fruit waste fermented with water, EM4, and molasses for 2–4 weeks. The effectiveness of the activity was evaluated by assessing students' knowledge gains using pre- and post-tests. The results demonstrated an improvement in students' understanding of LOF concepts, production techniques, and their benefits after participating in the training. Furthermore, monitoring results indicated that the produced LOF had appropriate fermentation characteristics, including a brownish colour, a distinct acidic fermentation odour, and a pH value of approximately 5, indicating its suitability for plant application. This activity contributed to improving students’ knowledge, practical skills, and environmental awareness, particularly in promoting sustainable organic waste management and encouraging environmentally friendly practices within the school environment.